2020
DOI: 10.3390/diagnostics10040222
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cytokines and Airways Disease Severity in Patients with Cystic Fibrosis

Abstract: About 50% of patients with cystic fibrosis (CF) have sinonasal complications, which include inferior turbinate hypertrophy (NTH) and/or nasal polyposis (NP), and different degrees of lung disease, which represents the main cause of mortality. Monitoring of sinonasal disease requires complex instrumental procedures, while monitoring of lung inflammation requires invasive collection of bronchoalveolar lavage fluid. The aim of this study was to investigate the associations between salivary cytokines levels and CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The studies that targeted salivary cytokines as OSCC biomarkers reported a strong relationship between their high levels and the presence of OSCC [ 18 , 49 , 51 , 53 , 54 , 55 , 56 , 57 , 60 , 61 , 62 , 63 , 64 ]. Further challenges consist in ruling out other possible causes that could determine the increase of salivary cytokines, such as periodontitis, cystic fibrosis, Sjögren’s syndrome, and acute stress [ 13 , 19 , 71 , 72 ]. Taking these facts into consideration, besides an oral cancer screening tool that utilizes cytokine biomarkers, it is important to evaluate general health and oral statuses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies that targeted salivary cytokines as OSCC biomarkers reported a strong relationship between their high levels and the presence of OSCC [ 18 , 49 , 51 , 53 , 54 , 55 , 56 , 57 , 60 , 61 , 62 , 63 , 64 ]. Further challenges consist in ruling out other possible causes that could determine the increase of salivary cytokines, such as periodontitis, cystic fibrosis, Sjögren’s syndrome, and acute stress [ 13 , 19 , 71 , 72 ]. Taking these facts into consideration, besides an oral cancer screening tool that utilizes cytokine biomarkers, it is important to evaluate general health and oral statuses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the changes determined by OSCC may be detected in saliva at the genomic, transcriptomic, and proteomic levels [ 11 ]. Also, recent proteomic studies of saliva provided new information that correlates salivary proteins/peptides in general and cytokines in particular with various pathological states [ 12 , 13 , 14 , 15 , 16 ]. The study performed by Kosaka et al [ 14 ] mentions a strong relationship between the increased interleukin (IL)-6 and tumor necrosis factor (TNF)-α levels and the incidence of atherosclerosis found in their study group [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the liver status and the presence of CF liver disease (CFLD) were evaluated on the basis of clinical, biochemical and U/S scanning (if necessary) results. The evaluation of sinonasal pathology was performed by clinical evaluation followed by rhinoscopy and, if necessary, by TC scanning, as described [ 18 ]. Furthermore, we recorded other complications, i.e., meconium ileus, metabolic alkalosis and distal intestine obstructive syndrome (DIOS) as described [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dysregulation of epithelial cells and innate immune function in the lungs results in increased, albeit ineffective, inflammation [ 8 ]. CF patients show progressive deterioration of lung function associated with the increased production of pro-inflammatory cytokines such as tumour necrosis factor α (TNFα), interleukin-6 (IL-6), and IL-8 in serum and in saliva [ 9 , 10 ]. In this scenario, physical activity (PA) plays a pivotal role in the treatment of chronic diseases characterised by increased inflammation status, including metabolic pathologies [ 11 ].…”
Section: Introductionmentioning
confidence: 99%